PERDAGANGAN INTRA-INDUSTRI ASEAN-5 TERHADAP INDIA DAN KOREA SELATAN - Utami Baroroh (Signifikan: Jurnal Ilmu Ekonomi, 2015)
The aim of this research is to analyze the export product competitive advantage and trade’s flow in Indonesia and ASEAN to India and South Korea. Besides that, this research also mapping the opportunity and threat that show by Indonesian export characteristics through it competency and the composition of export products. The variables that used in this research are the total trade of iron ore, machine, and automotive from each countries, the world’s total trade, and export total from each countries. The methods that used were intra-industry trade (IIT) index and revealed comparative advantage (RCA). The result shows that in general the intra-industry trade for iron ore, machine, and automotive commodities in ASEAN-5 region and also India and South Korea in medium integration level. This implied the low dependency in economy. Besides that, the competition intensity level Indonesia to ASEAN-5 regions, India, and South Korea is decreasingDOI: 10.15408/sjie.v4i1.2292